LCST behavior of poly(2-ethyl-2-oxazoline) containing diblock and triblock copolymers. (March 2018) - Sahn, Martin; Stafast, Leanne M.; Dirauf, Michael; Bandelli, Damiano; Weber, Christine; Schubert, Ulrich S.
Graphical abstract: Highlights: Well-defined diblock copolymers comprising PEtOx, P(eTEGA) or PNiPAm can be obtained. Tailor-made triblock copolymers comprising PEtOx and P(eTEGA) can be prepared. Hydrophobic end groups affect the LCST behavior of the triblock copolymers. Intramolecular hydrogen bonding does not influence the LCST behavior of the copolymers. The PNiPAm block collapses independently from a sufficiently long PEtOx block. Abstract: Mono- and bifunctional macro chain transfer agents were prepared via the living cationic ring opening polymerization of EtOx. A series of well-defined P(eTEGA)- b -PEtOx- b -P(eTEGA) triblock copolymers, PEtOx- b -P(eTEGA) as well as PEtOx- b -PNiPAm diblock copolymers were obtained by subsequent reversible addition fragmentation chain transfer polymerization of eTEGA or NiPAm, respectively. While the molar mass of the PEtOx was kept constant, the DP of the PNiPAm or P(eTEGA) block was varied and covers a wide range. Turbidimetry, NMR spectroscopy and dynamic light scattering investigations of the aqueous polymer solutions revealed that the lower critical solution temperature behavior of the triblock copolymers is strongly affected by the hydrophobic end groups whereas the presence of hydrogen bond donating moieties does not play any role. For diblock copolymers with a sufficiently long PEtOx block, the PNiPAm blocks collapsed independently, resulting in multiple phase transitions and the formation of well-defined aggregated structures.